2022
DOI: 10.1002/ajb2.16032
|View full text |Cite
|
Sign up to set email alerts
|

First‐year Acacia seedlings are anisohydric “water‐spenders” but differ in their rates of water use

Abstract: Premise: First-year seedlings (FYS) of tree species may be a critical demographic bottleneck in semi-arid, seasonally dry ecosystems such as savannas. Given the highly variable water availability and potentially strong FYS-grass competition for water, FYS water-use strategies may play a crucial role in FYS establishment in savannas and, ultimately, in tree-grass competition and coexistence. Methods: We examined drought responses in FYS of two tree species that are dominant on opposite ends of an aridity gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
(98 reference statements)
4
5
0
Order By: Relevance
“…On the other hand, although our extensive sap flow measurements encompassed a wide range of soil moisture contents including dry conditions, we found no evidence suggesting that transpiration was limited by VPD, which suggests a water-spending strategy. This classification is further supported by a previous study that found an anisohydric water-spending strategy in one-year-old S. mellifera seedlings, although strategies may differ across life stages(Cory et al, 2022). We suppose that the water spending strategy of S. mellifera is enabled by a xylem architecture characterised by narrow and short vessels, which prevents xylem embolism and allows sap flow to be maintained under dry conditions(Hacke & Sperry, 2001).Across all three woody species, we found that sap flow is strongly positively correlated with shallow soil moisture (10 cm depth), indicating potentially intense competition with shallow-rooted grasses.A correlation between sap flow and soil moisture at a depth of 50 cm is found for C. mopane and C. alexandri.…”
supporting
confidence: 83%
“…On the other hand, although our extensive sap flow measurements encompassed a wide range of soil moisture contents including dry conditions, we found no evidence suggesting that transpiration was limited by VPD, which suggests a water-spending strategy. This classification is further supported by a previous study that found an anisohydric water-spending strategy in one-year-old S. mellifera seedlings, although strategies may differ across life stages(Cory et al, 2022). We suppose that the water spending strategy of S. mellifera is enabled by a xylem architecture characterised by narrow and short vessels, which prevents xylem embolism and allows sap flow to be maintained under dry conditions(Hacke & Sperry, 2001).Across all three woody species, we found that sap flow is strongly positively correlated with shallow soil moisture (10 cm depth), indicating potentially intense competition with shallow-rooted grasses.A correlation between sap flow and soil moisture at a depth of 50 cm is found for C. mopane and C. alexandri.…”
supporting
confidence: 83%
“…A recent experiment by Cory et al. (2022) demonstrated that V. tortilis seedlings transpire and drain soil moisture faster than V. robusta , which contributed to faster drying and, in our case, thinner stems (Figure 2c) and low survival (Figure 3). Alternatively, poor stem growth of V. tortilis relative to V. robusta seedlings could be attributed to differences in water use efficiency under competition.…”
Section: Discussionsupporting
confidence: 49%
“…The fact that V. robusta seedlings stems did better than V. tortilis, especially under unclipped grasses, but poorly under grass removal may be related to their difference in transpiration rates and water use. A recent experiment by Cory et al (2022) demonstrated that V. tortilis seedlings transpire and drain soil moisture faster than V. robusta, which contributed to faster drying and, in our case, thinner stems (Figure 2c) and low survival (Figure 3). Alternatively, poor stem growth of V. tortilis relative to V. robusta seedlings could be attributed to differences in water use efficiency under competition.…”
Section: F I G U R Esupporting
confidence: 45%
See 2 more Smart Citations